Mapping global research trends in socioemotional skills interventions: a bibliometric analysis (1970–2025) - Richard Rickie Akat; Suziyani Mohamed; Nurul Khairani Ismail (International Journal of Evaluation and Research in Education (IJERE), 2026)
This study examines global research trends in socioemotional skills interventions through a bibliometric analysis of 687 Scopus-indexed publications (1970–2025). Using Bibliometrix and VOSviewer, the study analyses publication growth, influential contributors, and thematic structures. Results show a sharp increase in publications after 2015, with the United States dominating research output and citation impact. Keyword co-occurrence analysis identifies “social emotional learning” and “socioemotional skills” as the conceptual core, while early childhood and autism-related interventions remain underrepresented. The results reveal a core–periphery knowledge structure dominated by universal school-based frameworks, highlighting critical gaps in population-specific socioemotional intervention research.